A Shared Food Source Is Not Necessary to Elicit Inequity Aversion in Dogs - McGetrick, Jim; Ausserwöger, Sabrina; Leidinger, Ingrid; Attar, Claudia; Range, Friederike (Frontiers in Psychology, 2019)
Cooperative interactions frequently result in the acquisition of resources that have to be shared. Distribution of such resources should be equitable for cooperation to be beneficial. One mechanism thought to maintain cooperation through promotion of equitable reward distribution is inequity aversion, the resistance to inequitable outcomes. Inequity aversion has been demonstrated in many non-human animal species. It is not yet clear whether inequity aversion is limited to situations in which resources are shared; however, a recent study on inequity aversion in dogs, in which reward sources were separated, failed to elicit inequity aversion, hinting at the possible necessity of a shared resource for eliciting inequity aversion. Here, we employed a modified version of the previously used paw task to test the hypothesis that a shared food source is necessary to elicit inequity aversion in dogs. In our study, an experimenter asked pairs of dogs for their paw and rewarded them equally or unequally; however, unlike the standard paw task, the rewards for each dog came from separate food bowls. Dogs displayed the typical basic aversion to inequity despite the lack of a shared food source. These results suggest that a shared food source is not necessary to elicit inequity aversion and that separation of food sources does not explain the recent failure to elicit inequity aversion in dogs. Our findings may also be reflective of the variety of situations in which inequity aversion is potentially applied, the mechanisms underlying inequity aversion in dogs, and the behavioural contexts from which inequity aversion initially evolved.